2010
DOI: 10.1002/elan.200900404
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanoporous Binary AuRu Electrocatalysts for Glucose Oxidation

Abstract: In this work, we study the fabrication, structural characterization, and electrochemical activity of titanium-supported binary AuÀRu catalysts for glucose oxidation. The catalysts including Au 99 Ru 1 , Au 95 Ru 5 , Au 93 Ru 7 and Au 88 Ru 12 were prepared by a hydrothermal method using formaldehyde as a reduction agent. The morphologies of the prepared AuÀRu catalyst structures are characterized by porous dendritic particles with roughened surfaces with nano-sized flakes. Electrochemical catalytic activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…[2,14,17] In addition, other works showed that a good performance in glucose oxidation was obtained at different ratios of 2 metals not equal to 1:1 (Pd1Pt0.37, Pd30Au70, and Au95Ru5). [13,15,32] In case of the metal-loaded graphene catalyzed glucose electrooxidation research, most of the study was related to the glucose sensing, [17,33,34] the study focused on their electrocatalytic activity in the glucose electrooxidation was relatively few in number. [35,36] Moreover, most of the activity study was focused on the single cycle activity only, [2, 13-15, 17, 35] the systematic study in influence of glucose and hydroxide (OH -) concentrations on the glucose electrooxidation of the metal-loaded catalytic electrodes was relatively few in number, [2,6] graphene based one with long term stability together was even rare.…”
Section: Introductionmentioning
confidence: 99%
“…[2,14,17] In addition, other works showed that a good performance in glucose oxidation was obtained at different ratios of 2 metals not equal to 1:1 (Pd1Pt0.37, Pd30Au70, and Au95Ru5). [13,15,32] In case of the metal-loaded graphene catalyzed glucose electrooxidation research, most of the study was related to the glucose sensing, [17,33,34] the study focused on their electrocatalytic activity in the glucose electrooxidation was relatively few in number. [35,36] Moreover, most of the activity study was focused on the single cycle activity only, [2, 13-15, 17, 35] the systematic study in influence of glucose and hydroxide (OH -) concentrations on the glucose electrooxidation of the metal-loaded catalytic electrodes was relatively few in number, [2,6] graphene based one with long term stability together was even rare.…”
Section: Introductionmentioning
confidence: 99%
“…DA, AA, UA, sucrose, lactose, d‐fructose and Cl − [68]; (II) under alkaline environment, the interferents like UA and AA would also be deprotonated to form negatively charged molecules, which were repelled far away from the CuS nanowall electrode by electric field force [69]; (III) the applied potential (0.33 V) was low enough to avoid the extensive oxidation of UA and AA [3]. Of significance was that the quite small value (0.58 %) implied that the chloride poisoning effect on 2‐D CuS‐NWAs electrode can be eliminated, which advantaged over the ones based on metals and its alloys [21–30]. In all, the as‐obtained CuS‐NWAs sensor for nonenzymatic glucose detection bore a high selectivity and poison resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Au [21], Pt [22, 23], Pd [24], Cu [25], Ni [26]), bimetallic (Ni@Cu [27]), metal alloys ( e. g . Pt 2 Pb [28], PtAu [29], AuRu [30]) have been employed as non‐enzymatic sensors, the intermediate absorbing and chloride‐ion poisoning can seriously decline the sensitivity of non‐enzymatic glucose sensors. Moreover, the high cost of noble metals has hampered the further application [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent [104]); metal oxides (copper oxide [105], cobalt oxide [106], nickel oxide [107], manganese oxide [108], zinc oxide [109], iron oxide [110]); metal complexes (nickel hexacyanoferrate [111]); alloys (platinum-Lead [112], platinum-ruthenium [113], platinum-iridium [114], platinum-nickel [115], platinum-gold [116], gold-silver [117], gold-ruthenium [118], gold-copper [119]), nickel oxide/carbon [120], platinum/nickel oxide [121], copper/nickel oxide [122], copper/zinc oxide [123], copper/copper oxide [124], palladium/copper oxide [125], titanium dioxide/copper oxide [126], cadmium oxide/nickel oxide [127]); quantum dots (cadmium telluride [128], zinc sulfide [129], cadmium sulfide [130]); polymers (polyaniline [131], N-isopropylacrylamide [132]); and carbon based materials (fullerene [133], carbon nanotubes and graphene [134], carbon nanofibers [135]). This review has concentrated solely on presenting the exclusive nature of electrospun nanofibers and their composites for the efficient development of glucose sensors.…”
Section: Overview Of Glucose Sensor Developmentmentioning
confidence: 99%